2012
DOI: 10.1111/j.1753-0237.2012.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Oil price shocks and stock market in oil‐exporting countries: evidence from Iran stock market

Abstract: This study adopts causality in mean and variance approach to investigate dynamic relationship between stock market in an oil‐exporting country (Iran) and the international oil market. The empirical results imply that in view of underlying data‐generating process of the series, the variance of oil price fluctuations does not cause the variance of Iran stock returns. This means that there is no volatility spillover effect between Iran stock market and international oil market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…This follows with an increase in the productivity and lowering of unemployment. These results are coinciding with some of the prior works (Nguyen et al, 2020;Oskooe, 2011), accordingly the study can reject the fourth hypothesis (see Table 4).…”
Section: Regression Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…This follows with an increase in the productivity and lowering of unemployment. These results are coinciding with some of the prior works (Nguyen et al, 2020;Oskooe, 2011), accordingly the study can reject the fourth hypothesis (see Table 4).…”
Section: Regression Modelsupporting
confidence: 89%
“…A study was conducted in Iran to test the dynamic relationship between oil prices and the stock market for weekly data for the period (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), and concluded that the variation in oil prices does not cause any variation in share prices, bearing the absence of any impact of the international oil markets on the Iranian stock market (Oskooe, 2011). Meanwhile, a mixed study attempted to find the degree of overlap between oil prices and stock market indicators in a group of importing and exporting oil using monthly data for the period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010).…”
Section: Oil Price and Stock Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it was established that higher oil prices and higher revenues do not translate into sustained economic growth. However, Oskooe () established that there is no volatility spill‐over effect between Iran stock market (an oil exporting country) and international oil market. In another study by Onour (), it was established that the influence of oil price change on Gulf Cooperation Council (GCC) stock market is long term rather than short term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bhar and Nikolova (2010) found that changes in global oil prices have a significant impact on the level of equity returns and volatility in the Russian equity markets. Oskooe (2012) found that the variance of oil price fluctuations does not cause the variance of stock returns in Iran, while Babatunde et al (2013) documented that stock returns in Nigeria exhibit insignificant positive response to oil price shocks.…”
mentioning
confidence: 99%